Rancang Bangun Mobile Secure Chat dengan Mengimplementasikan Metodologi SSDLC-Agile dan Kriptografi - Hermawan Setiawan; Akhmad Rizal (Jurnal Ilmiah SINUS, 2023)
Along with the times, the exchange of information is becoming faster. People now use chat applications as a form of communication. With this application, users can easily exchange messages, whether in the form of text, images, audio, or video, without being limited by differences in distance and time. The information circulating varies, ranging from unclassified, private, to maybe confidential. Therefore, an encryption-decryption mechanism is needed so that users can exchange information safely through the mobile chat application. This study aims to implement the Rabin cryptosystem, symmetric encryption, and the use of session keys in a secure chat infrastructure for mobile applications. The test results showed that the combination of cryptographic applications and the Secure SDLC can increase security in application development, in this case for mobile secure chat.